Erk5 in Bone Marrow Mesenchymal Stem Cells Regulates Bone Homeostasis by Preventing Osteogenesis in Adulthood. Issue 4 (22nd February 2022) - Horie, Tetsuhiro; Fukasawa, Kazuya; Yamada, Takanori; Mizuno, Seiya; Iezaki, Takashi; Tokumura, Kazuya; Iwahashi, Sayuki; Sakai, Shiho; Suzuki, Akane; Kubo, Takuya; Osumi, Ryoma; Tomizawa, Akane; et al.
Abstract: Extracellular signal-regulated kinase 5 (Erk5) belongs to the mitogen-activated protein kinase (MAPK) family. Previously, we demonstrated that Erk5 directly phosphorylates Smad-specific E3 ubiquitin protein ligase 2 (Smurf2) at Thr 249 (Smurf2 Thr249 ) to activate its E3 ubiquitin ligase activity. Although we have clarified the importance of Erk5 in embryonic mesenchymal stem cells (MSCs) on skeletogenesis, its role in adult bone marrow (BM)-MSCs on bone homeostasis remains unknown. Leptin receptor-positive (LepR + ) BM-MSCs represent a major source of bone in adult bone marrow and are critical regulators of postnatal bone homeostasis. Here, we identified Erk5 in BM-MSCs as an important regulator of bone homeostasis in adulthood. Bone marrow tissue was progressively osteosclerotic in mice lacking Erk5 in LepR + BM-MSCs with age, accompanied by increased bone formation and normal bone resorption in vivo. Erk5 deficiency increased the osteogenic differentiation of BM-MSCs along with a higher expression of Runx2 and Osterix, essential transcription factors for osteogenic differentiation, without affecting their stemness in vitro. Erk5 deficiency decreased Smurf2 Thr249 phosphorylation and subsequently increased Smad1/5/8-dependent signaling in BM-MSCs. The genetic introduction of the Smurf2 T249E mutant (a phosphomimetic mutant) suppressed the osteosclerotic phenotype in Erk5 -deficient mice. These findings suggest that the Erk5-Smurf2 Thr249 axis in BM-MSCs plays a critical role in the maintenance of proper bone homeostasis by preventing excessive osteogenesis in adult bone marrow. Graphical Abstract: